Innovation and Practice of Teaching Models and Practical Training Systems for International Cruise Stewardship Management Major Based on Digital Twin Technology - Jiang, Rui; Zhang, Xiaowei (Journal of Educational Research and Policies, 2025)
This study addresses the teaching challenges in International Cruise Stewardship Management by establishing an innovative “virtual-real integration and dual-track parallel” teaching model and four-dimensional integrated training system based on Digital Twin Technology, which achieves deep integration of job skills, courses, competitions, and certificates through 3D scenario simulation, intelligent learning, and school-enterprise collaborative training. Practical results demonstrate that this system significantly enhances students’ job competence and enterprise satisfaction, providing a replicable practical solution for the digital transformation of vocational education.